FERMI LARGE AREA TELESCOPE OBSERVATIONS OF THE SUPERNOVA REMNANT W28 (G6.4-0.1) - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
We present detailed analysis of two gamma-ray sources, 1FGL J1801.3-2322c and 1FGL J1800.5-2359c, that have been found toward the supernova remnant (SNR) W28 with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope. 1FGL J1801.3-2322c is found to be an extended source within the boundary of SNR W28, and to extensively overlap with the TeV gamma-ray source HESS J1801-233, which is associated with a dense molecular cloud interacting with the SNR. The gamma-ray spectrum measured with the LAT from 0.2 to 100 GeV can be described by a broken power-law function with a break at similar to 1 GeV and photon indices of 2.09 +/- 0.08 (stat) +/- 0.28 (sys) below the break and 2.74 +/- 0.06 (stat) +/- 0.09 (sys) above the break. Given the clear association between HESS J1801-233 and the shocked molecular cloud and a smoothly connected spectrum in the GeV-TeV band, we consider the origin of the gamma-ray emission in both GeV and TeV ranges to be the interaction between particles accelerated in the SNR and the molecular cloud. The decay of neutral pions produced in interactions between accelerated hadrons and dense molecular gas provides a reasonable explanation for the broadband gamma-ray spectrum. 1FGL J1800.5-2359c, located outside the southern boundary of SNR W28, cannot be resolved. An upper limit on the size of the gamma-ray emission was estimated to be similar to 16' using events above similar to 2 GeV under the assumption of a circular shape with uniform surface brightness. It appears to coincide with the TeV source HESS J1800-240B, which is considered to be associated with a dense molecular cloud that contains the ultra compact H II region W28A2 (G5.89-0.39). We found no significant gamma-ray emission in the LAT energy band at the positions of TeV sources HESS J1800-230A and HESS J1800-230C. The LAT data for HESS J1800-230A combined with the TeV data points indicate a spectral break between 10 GeV and 100 GeV.
CRIS-Team WoS Importer:2020-01-15